MULTIPLE ENDOCRINE NEOPLASIA TYPE 2A WITH ECTOPIC ACTH SYNDROME DUE TO BILATERAL PHEOCHROMOCYTOMA - Kaewcharoen , Wimalin; Payanundana, Manaporn (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Ectopic ACTH syndrome (EAS) accounts for less than 5% of endogenous Cushing’s syndrome. In a previous retrospective study on patients with endogenous Cushing’s syndrome, only one had EAS from pheochromocytoma. A 33-year-old Thai female with a cushingoid appearance complained of abdominal pain. CT scan showed an enlarged bilateral adrenal gland. Urine VMA was positive. 1 mg dexamethasone suppression test and 24 hr urine-free cortisol suggested endogenous hypercortisolism. Plasma ACTH was 21 pg/ml, not suppressible on high-dose dexamethasone suppression test. She was subsequently diagnosed with bilateral pheochromocytoma with ectopic ACTH and underwent bilateral adrenalectomy. Her genetic testing showed a heterozygous pathogenic variant in the RET gene (c.1901G>A,p.Cys634Tyr), consistent with MEN2. Serum calcitonin was 121 pg/ml. She eventually underwent a total thyroidectomy as well. Genetic testing is beneficial for the diagnosis of symptoms related to genetic pheochromocytoma. It is also beneficial for screening family members and finding tumors at other locations.